Split application of varying potassium (K) rates influence wheat yield and K use efficiency - Khatun, Sufia; Zaman, Farhana; Hossain, Md Mosaraf; Sarker, Mohammad Joyel; Hasan, Ahmed Khairul (Fundamental and Applied Agriculture, 2022)
Potassium (K) application during land preparation doesn’t meet the crop requirement as huge amount of K is lost. Moreover, dose also should be optimized considering land, soil and variety. Therefore, a field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, to explore the influence of different management levels of K on yield and potassium use efficiency of wheat. Two wheat varieties (BARI Gom-27 and BARI Gom-33) and nine potassium (K) management levels [K0 = 0 kg K ha-1, K1 = 40 kg K ha-1 (full as basal), K2 =40 kg K ha-1 (half as basal and half at active tillering stage), K3 = 60 kg K ha-1 (full as basal), K4 = 60 kg K ha-1 (half as basal and half at active tillering stage), K5 = 80 kg K ha-1 (full as basal), K6 = 80 kg K haha-1 (half as basal and half at active tillering stage), K7 =100 kg K ha-1 (full as basal), K8 = 100 kg K ha-1 (half as basal and half at active tillering stage)] were used as treatments. The results of potassium management levels revealed that yield and yield components of wheat except straw yield were increased with the split application of potassium (K) (half as basal + half at active tillering stage) at 80 kg ha-1 and decreased with no potassium (K) application. The highest grain yield (4.37 t ha-1 ) was obtained from 80 kg K ha-1 applied as split which was 69.37% higher than the control. The potassium agronomic efficiency (5.50%) and apparent potassium recovery efficiency (29.17 kg kg-1) were highest in the treatment application of potassium at 40 kg ha-1 (half as basal and half at active tillering stage) grown with BARI Gom-33. In split application and 80 kg K ha-1 condition BARI Gom-33 gave the highest grain yield (4.77 t ha-1 ). Therefore, it may be concluded that the application of 80 kg K ha-1 as split (half as basal and half at active tillering stage) may be followed to achieve higher yield in wheat cultivation.